2019
DOI: 10.1016/j.dental.2018.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Biostable, antidegradative and antimicrobial restorative systems based on host-biomaterials and microbial interactions

Abstract: Objectives: Despite decades of development and their status as the restorative material of choice for dentists, resin composite restoratives and adhesives exhibit a number of shortcomings that limit their long-term survival in the oral cavity. Herein we review past and current work to understand these challenges and approaches to improve dental materials and extend restoration service life. Methods: Peer-reviewed work from a number of researchers as well as our own are summarized and analyzed. We also includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 114 publications
0
51
0
Order By: Relevance
“…Utilizing drug-carrier particles to store and release drugs without forming voids can bypass these problems and prolong release by the limited diffusion of media into the particle, and subsequent diffusion of the drug out [ 49 ]. Mesoporous silica nanoparticles (MSNs) are a promising carrier that can store large amounts of drugs in their pores and extend release by limiting drug diffusion [ 50 ].…”
Section: Current Antimicrobial Strategies Of Resin Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing drug-carrier particles to store and release drugs without forming voids can bypass these problems and prolong release by the limited diffusion of media into the particle, and subsequent diffusion of the drug out [ 49 ]. Mesoporous silica nanoparticles (MSNs) are a promising carrier that can store large amounts of drugs in their pores and extend release by limiting drug diffusion [ 50 ].…”
Section: Current Antimicrobial Strategies Of Resin Compositesmentioning
confidence: 99%
“…However, the effect of biodegradation on many antimicrobial monomers is unknown. For those which contain unprotected and easily hydrolyzed bonds, degradation may happen and thus release toxic degradation products, even though they are covalently attached to the matrix [ 49 ]. In sum, the long-term biocompatibility of antimicrobial modified resin composites should be studied.…”
Section: Challenges Faced By Antimicrobial Dental Restorationsmentioning
confidence: 99%
“…Patient characteristics include high caries-risk, gingival cavity margins, and posterior teeth [ 15 ]. Indeed, most dental resins are degraded by the caustic conditions present in the oral cavity and this activity leads to the long-term release of degradation by-products [ 16 , 17 ]. These by-products accumulate at the resin/tooth interface and increase the virulence of cariogenic bacteria, provoking a degradative positive-feedback loop [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, most dental resins are degraded by the caustic conditions present in the oral cavity and this activity leads to the long-term release of degradation by-products [16,17]. These by-products accumulate at the resin/tooth interface and increase the virulence of cariogenic bacteria, provoking a degradative positive-feedback loop [16]. This degradative feedback loop is central to the failure of dental adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…The interface between tooth and orthodontic bonding adhesive or cement, many of them based on (meth)acrylate chemistry, could also become the victim of bacterial attack and subsequent degradation [ 20 , 21 ]. Finer et al’s findings revealed increased degradation of resin-based composite and bonding agent by S. mutans UA159 vs. control.…”
Section: Introductionmentioning
confidence: 99%